Pilot testing of a heat integrated 0.7 MWe CO2 capture system with two-stage air-stripping: Emission. (September 2017) - Thompson, Jesse G.; Combs, Megan; Abad, Keemia; Bhatnagar, Saloni; Pelgen, Jonathan; Beaudry, Matthew; Rochelle, Gary; Hume, Scott; Link, David; Figueroa, Jose; Nikolic, Heather; Liu, Kunlei
Graphical abstract: Highlights: A 0.7 MWe pilot post-combustion CO2 capture unit with 2-stage stripping was tested. Emissions were monitored to determine the impact of the secondary air stripper. Ammonia emission strongly correlated with solvent Fe and Cu in the solvent. Emission levels were comparable to previously published reports with 30% MEA. The impact of the secondary air stripper on solvent oxidation was negligible. Abstract: The University of Kentucky Center for Applied Energy Research (UKy-CAER) designed, constructed and tested an advanced 0.7 MWe post-combustion CO2 capture system on a coal-fired power plant using a heat integration process combined with two-stage stripping to enhance the CO2 absorber performance and lower the cost of CO2 capture. Evaluation of emissions from the solvent and degradation products was performed to determine the impact on the amine solvent of coal combustion flue gas contaminants and oxygen exposure due to incorporation of the secondary air stripper into the conventional amine absorber/stripper system. The overall amine, ammonia and aldehyde emission levels observed during the baseline 30% monoethanolamine (MEA) solvent testing campaign were generally comparable to previously published reports tested at similar flue gas conditions and system operating hours. Ammonia emissions were correlated to high levels of iron and copper in the solvent, likely as a result of material corrosion.